Comparative Study of Protein Expression Levels of Five Plaque Biomarkers and Relation with Carotid Plaque Type Classification in Patients after Carotid Endarterectomy - Konstantinos Kyriakidis; Pavlos Antoniadis; Sohail Choksy; Rigini M. Papi (International Journal of Vascular Medicine)
Atherosclerosis is an inflammatory process resulting in local plaque deposition in the vessel wall of arteries with symptoms to various areas of vascular tree. Identification of patients with progressive advanced atherosclerotic disease is mainly based on the known characteristics of the vulnerable or recently ruptured plaque. Molecular and cellular features associated with the vulnerable plaque are considered potential diagnostic markers for plaque rupture and thrombosis. Here, protein expression levels of the metalloproteases MMP-1, MMP-9, osteopontin (OPN), and cytokines TNFα and IL-6 in tissue extracts of carotid plaques in patients after endarterectomy were estimated by Western immunoblotting, after SDS-PAGE analysis and evaluated based on the ultrasonographic plaque morphology. The gender and age effect was also examined. MMP-1, MMP-9, and IL-6 were expressed in higher levels compared to OPN and TNFa as well as in symptomatic (with type II and III carotid plaque classification) than asymptomatic (type IV) patients with differences considered statistically significant (P values <0.05). A significant positive correlation between MMP-1 and IL-6 (with Pearson correlation coefficient 0.748) is also notable. The data give further insight into the possible role of specific biomarker and enhance the need for further studies in order to clarify the proper one(s) for detection of the vulnerable plaque and help identify patients at risk for cardiovascular events.